Transient middle cerebral artery occlusion in rats as an experimental model of brain ischemia - Calloni,Renato Luis (2010)
PURPOSE: To assess a rat model of cerebral ischemia induced by occlusion of the middle cerebral artery and its effect on the area of cerebral infarction. METHODS: Brain ischemia was induced in 52 male Wistar rats by introduction of a 3-0 nylon suture into the middle cerebral artery for either 90 (n=28) or 120 (n=24) minutes. Ischemic injury volume was determined by TTC staining, digital photography and analysis with the Image J software. Statistical analysis employed Students t test and the Mann-Whitney U test. RESULTS: The groups were similar in terms of weight (p=0.59). The length of thread inserted was 14.7 mm in the 90 min group and 20.2 mm in the 120 min group (p=0.37). Ischemic injury was detected in 11 animals (39%) after 90 min and 11 (45%) after 120 min (p=0.77). In animals exhibiting injury, filament length was 16.1±11 mm (90 min) vs. 21.9±7.4 mm (120 min) (p=0.15). The mean infarction zone volume was greater after 120 (259.2 mm³) than after 90 min (162.9 mm³) (p=0.04). The neurological deficit score for the 90 and 120 min groups was 2.0 and 2.4, respectively (p=0.84). CONCLUSION: The experimental model induced significant ischemic cerebral injury in both groups.